A RARE CASE OF PRIMARILY MISDIAGNOSED GIANT MALIGNANT MIXED GERMINATIVE MEDIASTINAL TUMOR IN A YOUNG MALE PATIENT, SURGICALLY REMOVED BY “COLISEUM” APPROACH - Savić, Mlađana; Ristanović, Aleksandar; Petković, Miloš; Marić, Nebojša (Srpski medicinski časopis Lekarske komore, 2026)
Introduction: Mixed germ cell tumor (MGCT) is most common in younger patients and is localized primarily to the gonads. After reviewing the literature, we concluded that there are only a few cases of mediastinal MGCT – primary mediastinal MGCT accounts for about 10–15% of all mediastinal malignancies and up to 3% of all MGCT. Mediastinal MGCT with more than three pathological components, such as yolk sac tumor, teratoma, and embryonal carcinoma, has not been reported previously in the reviewed literature. Our patient had two more components (carcinoma and seminoma). Case report: The patient was a 40-year-old male who presented with chest pain and fever; chest CT showed a giant mass in the right pleural space, with a maximal diameter of 120 mm. Bronchoscopic findings were normal, and bronchial biopsies were negative. A combined open and VATS approach was used, which revealed NSCLC. The patient underwent chemotherapy, but the next CT scan of the thorax showed progression. Decision was made to perform surgical treatment – salvage pneumonectomy with “coliseum” approach. Intraoperatively, it was verified that the tumor origins were in the mediastinum, so the whole tumor was removed. The whole right lung was in atelectasis, but was not infiltrated by tumor – full reexpansion of the right lung was established during the surgery. The patient tolerated surgery well. Definitive PH finding showed that it was a mixed malignant germinative tumor. Urology findings and the postoperative full-body CT showed no signs of residual or recurrent tumor.Conclusion: The patient was initially misdiagnosed and treated with chemotherapy after the conclusion that he was not a candidate for surgical treatment. Primarily planned salvage surgery for this young patient ended as radical surgery and without the need for pneumonectomy.
Keywords: mixed germ cell tumor of mediastinum; misdiagnosed NSCLC; Colliseum approach; mediastinal tumors; surgical treatment